The Effect of Electric Field on Antioxidant Extraction from Avocado (Persea Americana) Seed - Faizah, Nurul; Widiyastuti, W.; Setyawan, Heru; Nurtono, Tantular (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
Avocado seeds have gained attention as a promising natural ingredient for various applications. Utilizing avocado seeds reduces food waste and improves sustainability. Avocado seed contains a high concentration of bioactive chemicals as natural antioxidants that scavenge free radicals. This study investigates the impact of electric field (EF) treatment on avocado seed extraction enhancement. The effect of electric field strength ranging from 2.5 to 7.5 kV/cm with a treatment time of 5 minutes was investigated. Extraction yield, FTIR analysis, antioxidant activity (via the DPPH radical scavenging assay), and IC₅₀ values were obtained from the experimental data. The data were analyzed to evaluate extraction performance and to determine free radical scavenging activity. The result indicates that the value of E influences the extraction result. The best extraction conditions was achieved at an electric field strength of 7.5 kV/cm. The highest performance was obtained using an electric field of 7.5 kV/cm with extraction yield 13.29%, antioxidant activity of 95%, and an IC50 concentration of 120 µg/mL. The FTIR spectrum shows several peaks at 3206, 2937, 1603, 1402, 1021, and 879 cm-1 representing OH, C-H stretch, C=C, -C-H stretch, C-O stretch, and in-plan deformation vibration CH, respectively, to indicate the presence of antioxidants. This study demonstrates that electric field-assisted extraction serves as an eco-friendly alternative to conventional methods for obtaining natural bioactive compounds from avocado seeds.